The development of academic mobility in Russian heis and the new fses - YU. . Artamonova; A. . Demchuk (Высшее образование в России)
The article contains statistical data, which reflects the modern state of academic mobilityin HEIs in the Russian Federation (the data was gathered while monitoring the efficiency of implementation of federal state educational standards (FSES) by HEIs). Its analysis is given, as well as a comparison of data, gathered as a result of polling and interviewing the authority of HEIs and its divisions with data from polls and interviews of students and professors, which gives a picture of academic mobility from two different angles.